ANALISIS POLA BELAJAR NUMERIK PADA ANAK TUNAGRAHITA DI SLB NEGERI CENDONO KUDUS - Martha Setiawati (STKIP Subang, 2023)
Writing this article aims to find out the pattern of numerical learning in mentally retarded children at the Cendono Kudus State SLB, this is oriented towards